Electromyographic Evaluation of Superior Orbicularis Oris Muscle Activity in Patients With Complete Cleft Lip and Cleft Palate Before and After Vestibuloplasty Using Carbon Dioxide Laser Therapy: Co2 laser therapy on Electromyography after vestibuloplasty in cleft lip patients - Yassaei, Soghra; Aghili, Hosseinagha; Salarpour, Elahe; Dehghan dehnavi, Ali (Journal of Lasers in Medical Sciences, 2022)
Introduction: Cleft lip and cleft palate are the most typical congenital craniofacial anomalies. Postsurgical scars in cleft lip patients can cause shallow upper labial sulcus and reduced upper lip length. The aim of the present study was to evaluate the impact of CO2 laser vestibuloplasty on the electromyographical (EMG) activity of patients’ superior orbicularis oris muscle, depth of labial sulcus, and upper lip length, and their satisfaction with the procedure and its results. The CO2 laser is an effective vestibuloplasty procedure, is safe and highly acceptable for patients, and has little effect on muscle contraction. Methods: A total of 15 cleft lip and cleft palate patients participated in this study. Vestibuloplasty was performed using carbon dioxide laser therapy in one session in such a way that EMG activity in the upper lip muscle, depth of labial sulcus, and upper lip length were measured two times: before (T0) and twenty days after surgery (T1). Patients’ satisfaction surveys were also recorded using a patient questionnaire at T1. Results: The mean values for vestibular depth at T0 and T1 were 2.00±1.71 and 4.52±1.43, respectively. The mean values for upper lip length at T0 and T1 were 6.90±2.32 and 8.00±2.40, respectively, suggesting a significant change in vestibular depth and upper lip length. The vestibular depth and upper lip length significantly increased at T1. The EMG recording of the upper lip muscle experienced a moderate decrease after laser treatment, both at rest and at maximum lip protrusion. Moreover, patient’s satisfaction with the surgical procedure was 82% positive. Conclusion: Using the CO2 laser increased the vestibular depth and upper lip length successfully and made small changes in the EMG activity of the superior orbicularis oris.